2005
DOI: 10.1097/01.brs.0000163885.12834.ca
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of the Scoliosis Quality of Life Index in Adolescent Idiopathic Scoliosis

Abstract: SQLI is reliable and valid and demonstrates satisfactory distribution of scores. SQLI is a promising instrument in the assessment of AIS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 16 publications
0
54
2
3
Order By: Relevance
“…18,46 -48 Studies of premorbid psychological traits in surgical patients suggest that patients high in trait anxiety and low in cognitive maturity, 35 and older patients 36 experience poorer psychological outcomes immediately following surgery (Table 3). In the Clayson et al study, 36 patients under the age of 15 years remained within the normal Approximately half of the women were or had been married (15), had children (14) and/or worked outside the home (13); all patients were judged to be of normal intelligence or above; a total of 18 patients were judged to suffer mental disturbance due to scoliosis (2 severe, 7 moderate, 9 slight; 10 had been psychiatric outpatients and 7 had a family history of mental illness); 16 patients were considered to have good or adequate socio-psychological functioning, 10 patients were considered to have good or adequate personality-psychological functioning; although the sample was small, patients with severe deformity (ϩϩϩ or ϩϩϩϩ), short in height, juvenile onset, loss in pulmonary functioning or high intelligence were rated as more poorly adjusted parameters on all dimensions of the California Psychological Inventory following surgery. Conversely patients over 16 years of age scored outside the normal range on several subscales on the Minnesota Multiphasic Personality Inventory before surgery, and scores became more pronounced following surgery.…”
Section: Psychosocial Issues In Patients With Scoliosismentioning
confidence: 94%
“…18,46 -48 Studies of premorbid psychological traits in surgical patients suggest that patients high in trait anxiety and low in cognitive maturity, 35 and older patients 36 experience poorer psychological outcomes immediately following surgery (Table 3). In the Clayson et al study, 36 patients under the age of 15 years remained within the normal Approximately half of the women were or had been married (15), had children (14) and/or worked outside the home (13); all patients were judged to be of normal intelligence or above; a total of 18 patients were judged to suffer mental disturbance due to scoliosis (2 severe, 7 moderate, 9 slight; 10 had been psychiatric outpatients and 7 had a family history of mental illness); 16 patients were considered to have good or adequate socio-psychological functioning, 10 patients were considered to have good or adequate personality-psychological functioning; although the sample was small, patients with severe deformity (ϩϩϩ or ϩϩϩϩ), short in height, juvenile onset, loss in pulmonary functioning or high intelligence were rated as more poorly adjusted parameters on all dimensions of the California Psychological Inventory following surgery. Conversely patients over 16 years of age scored outside the normal range on several subscales on the Minnesota Multiphasic Personality Inventory before surgery, and scores became more pronounced following surgery.…”
Section: Psychosocial Issues In Patients With Scoliosismentioning
confidence: 94%
“…16 Patients' perception of their body image affects their psychosocial health as scoliosis patients have been shown to have lower scores in various quality-of-life questionnaires compared to healthy adolescents. 17,18 Patients will closely observe their own physical appearance and make a comparison with adolescents without scoliosis in terms of negative body image, body shape and body size. 2 This will lead them to unhappier lives, more physical complaints, lower self-esteem and higher rate of depression.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was recently suggested that the SRS-22 questionnaire may not perform as well in the assessment of younger patients [10,11]. Specifically, higher ceiling effects have been reported using the SRS-22 questionnaire in different studies assessing groups of progressively younger participants [11,12].…”
Section: Introductionmentioning
confidence: 99%